Pertimbangan Hukum Judex Faxti Terhadap Putusan Lepas membuat atau memakai dokumen Palsu untuk mejadi bakal calon anggota DPRD Kabupaten Tanah Laut (Studi Putusan Mahkamah Agung Nomor: 199/PID.SUS/2023/PT/BJM) - Rahmiati, Rahmiati; Ridhanie, Azhar (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
This research aims to identify and describe the appropriateness of the judge's legal considerations in rendering a verdict of acquittal from all charges according to the applicable legal provisions, namely Law No. 7 of 2017 and Perbawaslu findings and Perbawaslu Sentra Gakkumdu reports. This study is normative legal research, also known as doctrinal legal research, which is conducted by studying and examining primary legal materials, secondary legal materials, and tertiary legal materials. Regarding primary legal materials, the author analyzes the legislation related to electoral criminal violations. Secondary legal materials used include journal articles, books, and research findings relevant to the research object. Additionally, tertiary legal materials used are legal dictionaries and language dictionaries. The analysis results show that in deciding a case, a judge must be based on the law and their conviction. The study indicates a discrepancy between the first court's decision, which convicted the defendant, and the appellate court's decision, which acquitted the defendant because the case was deemed time-barred. This decision does not align with the applicable formal law and the facts of the trial, demonstrating the inaccuracy of the panel of judges. The panel's consideration regarding the 1x24 hour time limit should follow electoral regulations, which stipulate the reporting and investigation process within a specific timeframe in accordance with Law No. 7 of 2017.